Lateralized Cerebral Processing of Abstract Linguistic Structure in Clear and Degraded Speech. (9th September 2020) - Meng, Qingqing; Hegner, Yiwen Li; Giblin, Iain; McMahon, Catherine; Johnson, Blake W
Abstract: Human cortical activity measured with magnetoencephalography (MEG) has been shown to track the temporal regularity of linguistic information in connected speech. In the current study, we investigate the underlying neural sources of these responses and test the hypothesis that they can be directly modulated by changes in speech intelligibility. MEG responses were measured to natural and spectrally degraded (noise-vocoded) speech in 19 normal hearing participants. Results showed that cortical coherence to "abstract" linguistic units with no accompanying acoustic cues (phrases and sentences) were lateralized to the left hemisphere and changed parametrically with intelligibility of speech. In contrast, responses coherent to words/syllables accompanied by acoustic onsets were bilateral and insensitive to intelligibility changes. This dissociation suggests that cerebral responses to linguistic information are directly affected by intelligibility but also powerfully shaped by physical cues in speech. This explains why previous studies have reported widely inconsistent effects of speech intelligibility on cortical entrainment and, within a single experiment, provided clear support for conclusions about language lateralization derived from a large number of separately conducted neuroimaging studies. Since noise-vocoded speech resembles the signals provided by a cochlear implant device, the current methodology has potential clinical utility for assessment of cochlear implant performance.